O ABSURDO DA MORTE NO NIILISMO DE BEAUVOIR E SCHOPENHAUER - Costa, Roberto Marques (Sapere Aude, 2021)
This article presents a basic and descriptive bibliographic research on death in the nihilistic conception of Beauvoir and Schopenhauer. Death is a natural, complex phenomenon that causes fear in individuals. Death is a fact for finitude, in which it reduces the human being to the absurdity of nothingness. The focus of the article is to discuss through secondary sources and by the hypothetical deductive method the problem of death in the philosophy of these two thinkers. The relevance of this scientific research is based on the insertion that death is an object of study of paramount importance, because it presents itself to the individual as an inexorable and imminent reality. In the philosophical theory of these authors, death is a fact that contains nothing but an absolute darkness. It is the finitude of all human